Kieliviesti, a Finnish language periodical from the Swedish Language Council - Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Kieliviesti is a Finnish language periodical on language cultivation from the Swedish Language Council. Content includes advice regarding terminology and translation as well as articles on topical Finnish language cultivation and language development. The periodical has four issues per year. 1980 - 1/2016.

Kieliviesti är Språkrådets finskspråkiga språkvårdstidskrift som även innehåller fyra sidor på meänkieli. I tidskriften publiceras term- och översättningsrekommendationer samt artiklar om aktuell finsk språkvård och om finska språkets utveckling. Vi informerar också om nyutkommen språkvårdslitteratur och om ordböcker. Kieliviesti utkommer med fyra nummer per år. 1980 - 1/2016.
Språkrådets finskspråkiga språkvårdstidskrift: Kieliviesti
Keywords: translation; översättning; Linguistics; Språkvetenskap; Periodical; Tidskrift [Publikationstyp]; glossary; ordlista; Language and linguistics; Språk och lingvistik; Languages and Literature; Språk och litteratur